Sitcom : a history in 24 episodes from I love Lucy to Community - Austerlitz, Saul (Chicago Review Press, 2014)
"Obsessively watched and critically ignored, sitcoms were a distraction, a gentle lullaby of a kinder, gentler America--until suddenly the artificial boundary between the world and television entertainment collapsed. In this book we track the growth of the sitcom, following the path that leads from I LOVE LUCY to THE PHIL SILVERS SHOW; from THE DICK VAN DYKE SHOW to THE MARY TYLER MOORE SHOW; from M*A*S*H to TAXI; from CHEERS to ROSEANNE; from SEINFELD to CURB YOUR ENTHUSIASM; and from THE LARRY SANDERS SHOW to 30 ROCK. In twenty-four episodes, SITCOM surveys the history of the form, and functions as both a TV mix tape of fondly remembered shows that will guide us to notable series and larger trends, and a carefully curated guided tour through the history of one of our most treasured art forms"--